Epidemiological survey of the feasibility of broadband ultrasound attenuation measured using calcaneal quantitative ultrasound to predict the incidence of falls in the middle aged and elderly. Issue 1 (9th January 2017) - Ou, Ling-Chun; Chang, Yin-Fan; Chang, Chin-Sung; Chiu, Ching-Ju; Chao, Ting-Hsing; Sun, Zih-Jie; Lin, Ruey-Mo; Wu, Chih-Hsing
Abstract : Objectives: We investigated whether calcaneal quantitative ultrasound (QUS-C) is a feasible tool for predicting the incidence of falls. Design: Prospective epidemiological cohort study. Setting: Community-dwelling people sampled in central western Taiwan. Participants: A cohort of community-dwelling people who were ≥40 years old (men: 524; women: 676) in 2009–2010. Follow-up questionnaires were completed by 186 men and 257 women in 2012. Methods: Structured questionnaires and broadband ultrasound attenuation (BUA) data were obtained in 2009–2010 using QUS-C, and follow-up surveys were done in a telephone interview in 2012. Using a binary logistic regression model, the risk factors associated with a new fall during follow-up were analysed with all significant variables from the bivariate comparisons and theoretically important variables. Primary outcome measures: The incidence of falls was determined when the first new fall occurred during the follow-up period. The mean follow-up time was 2.83 years. Results: The total incidence of falls was 28.0 per 1000 person-years for the ≥40 year old group (all participants), 23.3 per 1000 person-years for the 40–70 year old group, and 45.6 per 1000 person-years for the ≥70 year old group. Using multiple logistic regression models, the independent factors were current smoking, living alone, psychiatric drug usage and lower BUA (OR 0.93; 95% CI 0.88 to 0.99, p<0.05) in the ≥70 year old group. Conclusions: The incidence of falls was highest in the ≥70 year old group. Using QUS-C-derived BUA is feasible for predicting the incidence of falls in community-dwelling elderly people aged ≥70 years.